Two-wheel Tractor: A Versatile and Low-Cost Farm Power Source for the Smallholder Farmers - Matin, M. A.; Mulundu, S.; Zingwari, O. (2025)

(untitled)
The two wheel tractor (2WT) is a versatile and relatively affordable farm power option for smallholder farmers that can be used to power different farming operations, including conventional land preparation, ripping, ridge planting, seeding, spraying, weeding, threshing, pumping water, transportation, etc. It can improve the timeliness of farming operations, save time and labour, and enhance the quality of the farming operations. It reduces drudgery drastically and can attract more youth and women to agriculture. The two-wheel tractor has great potential for scaling in Zambia due to the relatively small landholding sizes among smallholder farmers.